Sex differences in axial spondyloarthritis - Cunha, R. N. (2022)
Background: Axial spondyloarthritis (axSpA), particularly ankylosing spondylitis was historically considered a male’s disease and has been under-recognized in women. Emerging evidence reveals sex differences in pathophysiology, disease presentation and therapeutic efficacy. Objective: To identify differences between sexes in a Portuguese cohort of patients with axSpA regarding clinical manifestations, disease activity, functional capacity, patient related outcomes and presence of sacroiliitis on x-ray or magnetic resonance imaging. Methods: Patients with ≥18 years fulfilling the ASAS-Assessment of Spondyloarthritis International Society classification criteria for axSpA registered in the electronic Rheumatic Diseases Portuguese Register (Reuma.pt) were included in this multicentric cross-sectional study. Sociodemographic data, clinical features and imaging were collected from the first record in Reuma.pt. These variables were compared between sexes using Mann-Whitney test and Chi-Square test. Variables with a significant association with variable sex were considered in the multiple variable analysis to adjust the sex effect on the outcome variables. Statistical analysis was performed with R version 4.0.2 and p<0.05 was considered statistically significant. Results: A total of 1995 patients were included, 1114 (55.9%) men and 881 (44.1%) women. Men had an earlier disease onset (25.1 vs 28.4, p<0.001), were younger at diagnosis (26.9 vs 30.4, p<0.001) and were more frequently smokers (32.1% vs 15.7%, p<0.001). Comparing to women, men had worse Bath Ankylosing Spondylitis Metrological Index scores (4.0 vs 3.4, p<0.001), higher levels of C-Reactive Protein (10.5 vs 6.9 mg/L, p<0.001) and were more often Human Leukocyte Antigen-B27 positive (67.8% vs 54%, p<0.001). In contrast, women more frequently had inflammatory bowel disease (8.8% vs 4.9%, p=0.004), higher levels of erythrocyte sedimentation rate (25.0 vs 21.0mm/h, p=0.003) and worse patient-related outcomes-Bath Ankylosing Spondylitis Disease Activity Index (5.7 vs 4.5, p<0.001), Patient Global Assessment (60.0 vs 50.0, p<0.001) and fatigue (6.2 vs 5.0, p<0.001). Discussion: In this large multicentric study from a Portuguese axSpA cohort, we confirmed sex differences in patients with axSpA. This work brings awareness to these differences, resulting in less underdiagnosis and misdiagnosis, optimizing treatment strategies, and improving outcomes in axSpA